Palliation of dyspnoea in advanced COPD: revisiting a role for opioids. Issue 10 (28th September 2009) - Rocker, G; Horton, R; Currow, D; Goodridge, D; Young, J; Booth, S
Abstract : Chronic obstructive pulmonary disease (COPD) will be the third leading cause of death worldwide by 2020. The burdens of this increasingly prevalent illness borne by patients, their family caregivers and the healthcare system are substantial. Dyspnoea as the predominant symptom becomes increasingly difficult to palliate as COPD progresses through advanced stages and, for 50% of patients, can become refractory to conventional treatment. This narrative review focuses on the potential role for carefully initiated and titrated opioids in the management of dyspnoea for patients with advanced COPD who are not yet in a terminal stage, yet struggle with symptoms that reflect underlying mechanisms of dyspnoea that lend themselves to this approach. The many barriers that currently exist to the provision of opioids in this setting are addressed, and recommendations are provided for an approach that should engender confidence among patients, their caregivers and the physicians who treat them.